ANALISIS PENGARUH LUAS KAWASAN HUTAN, KONSUMSI ENERGI FOSIL, DAN PERTUMBUHAN EKONOMI TERHADAP EMISI CO₂ DI INDONESIA - Fanny Nailufar; Mahyul Fattah (Jurnal Ekonomi Pertanian Unimal, 2025)
This study examines the influence of forest area, fossil fuel consumption, and economic growth on CO₂ emissions in Indonesia in the short- and long-term. Using secondary data from 1992 to 2023 obtained from the World Bank and Our World in Data, the analysis applies a dynamic Autoregressive Distributed Lag (ARDL) model with EViews. The results indicate that, in the short term, forest area positively and significantly affects CO₂ emissions, while fossil fuel consumption and economic growth negatively and significantly affect CO₂ emissions. In the long term, forest area has an insignificant negative effect, whereas fossil fuel consumption and economic growth show significant positive effects